2016
DOI: 10.1103/physrevb.94.115201
|View full text |Cite
|
Sign up to set email alerts
|

K-dependent exchange interaction of the1Sorthoexciton inCu2O

Abstract: When treating the exchange interaction of Wannier excitons, usually only the leading terms of the analytic and the nonanalytic exchange interaction are considered. However, higher order terms can lead to a splitting of exciton states, for which reason a splitting of the 1S exciton in cuprous oxide (Cu2O) depending on its total momentum K has been attributed to a K dependent analytic exchange interaction by Dasbach et al [Phys. Rev. Lett. 91, 107401 (2003)]. Going beyond the common treatment of the exchange int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…Even though the applied magnetic field breaks timereversal invariance, at least one antiunitary symmetry, e.g., time reversal and a certain parity, remains and GOE statistics is observed [1,22,23].Excitons are fundamental quasi-particles in semiconductors, which consist of an electron in the conduction band and a positively charged hole in the valence band.Recently, T. Kazimierczuk et al [24] have shown in a remarkable high-resolution absorption experiment an almost perfect hydrogen-like absorption series for the yellow exciton in cuprous oxide (Cu 2 O) up to a principal quantum number of n = 25. This experiment has drawn new interest to the field of excitons experimentally and theoretically [25][26][27][28][29][30][31][32][33][34][35].Since excitons in semiconductors are often treated as the hydrogen analog of the solid state but also show substantial deviations from this behavior due to the surrounding solid, the question about their level spacing statistics in external fields arises. First experimental investigations of the level spacing statistics in an external magnetic field give indications on a breaking of antiunitary symmetries, which is, however, attributed to the interaction of excitons and phonons [31].Very recently, we have shown that it is indispensable to account for the complete valence band structure of Cu 2 O in a quantitative theory of excitons [28] to explain the striking experimental findings of a fine structure splitting and the observability of F excitons [25].…”
mentioning
confidence: 99%
“…Even though the applied magnetic field breaks timereversal invariance, at least one antiunitary symmetry, e.g., time reversal and a certain parity, remains and GOE statistics is observed [1,22,23].Excitons are fundamental quasi-particles in semiconductors, which consist of an electron in the conduction band and a positively charged hole in the valence band.Recently, T. Kazimierczuk et al [24] have shown in a remarkable high-resolution absorption experiment an almost perfect hydrogen-like absorption series for the yellow exciton in cuprous oxide (Cu 2 O) up to a principal quantum number of n = 25. This experiment has drawn new interest to the field of excitons experimentally and theoretically [25][26][27][28][29][30][31][32][33][34][35].Since excitons in semiconductors are often treated as the hydrogen analog of the solid state but also show substantial deviations from this behavior due to the surrounding solid, the question about their level spacing statistics in external fields arises. First experimental investigations of the level spacing statistics in an external magnetic field give indications on a breaking of antiunitary symmetries, which is, however, attributed to the interaction of excitons and phonons [31].Very recently, we have shown that it is indispensable to account for the complete valence band structure of Cu 2 O in a quantitative theory of excitons [28] to explain the striking experimental findings of a fine structure splitting and the observability of F excitons [25].…”
mentioning
confidence: 99%
“…As we already stated in Ref. [14], a simple restriction to the Γ + 7 band neglecting the Γ + 8 band and considering the nonparabolicity of the Γ + 7 band via p 4 terms as has been done in Ref. [27] does not treat the problem correctly.…”
Section: A Band Structure Of Cu2omentioning
confidence: 99%
“…Recently, the yellow series could be followed up to a spectacular high principal quantum number of n = 25 [2]. This outstanding experiment has launched the new field of research of giant Rydberg excitons and led to a variety of new theoretical and experimental investigations on the topic of excitons in Cu 2 O [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%

The even exciton series in Cu$_2$O

Schweiner,
Main,
Wunner
et al. 2017
Preprint
Self Cite
“…For states of symmetry Γ + 5 it has been shown in Ref. [25] that the nonanalytic exchange interaction can be written as…”
Section: B 5 × 5 Matrix Modelmentioning
confidence: 99%